Comparative evaluation of debris extruded apically by using, Protaper retreatment file, K3 file and H-file with solvent in endodontic retreatment - Chetna Arora; Rohit Bahri; Neelam Mittal (Wolters Kluwer Medknow Publications, 2012)
Aim: The aim of this study was to evaluate the apical extrusion of debris comparing 2 engine driven systems and hand instrumentation technique during root canal retreatment. Materials and Methods: Forty five human permanent mandibular premolars were prepared using the step-back technique, obturated with gutta-percha/zinc oxide eugenol sealer and cold lateral condensation technique. The teeth were divided into three groups: Group A: Protaper retreatment file, Group B: K3, file Group C: H-file with tetrachloroethylene. All the canals were irrigated with 20ml distilled water during instrumentation. Debris extruded along with the irrigating solution during retreatment procedure was carefully collected in preweighed Eppendorf tubes. The tubes were stored in an incubator for 5 days, placed in a desiccator and then re-weighed. Weight of dry debris was calculated by subtracting the weight of the tube before instrumentation and from the weight of the tube after instrumentation. Data was analyzed using Two Way ANOVA and Post Hoc test. Results : There was statistically significant difference in the apical extrusion of debris between hand instrumentation and protaper retreatment file and K3 file. The amount of extruded debris caused by protaper retreatment file and K3 file instrumentation technique was not statistically significant. All the three instrumentation techniques produced apically extruded debris and irrigant. Conclusion: The best way to minimize the extrusion of debris is by adapting crown down technique therefore the use of rotary technique (Protaper retreatment file, K3 file) is recommended.